Implementation Of Blockchain Technology In Improving Information System Security - Adi Ahmad (Journal Informatic, Education and Management (JIEM), 2023)
The purpose of this research is to analyse the implementation of blockchain technology in improving information system security. The research method used is a literature study by collecting information from various relevant primary and secondary sources. The results of this study show that blockchain technology has strong potential to strengthen information system security through its unique characteristics, such as decentralisation, transparency, and high cryptographic security. While analysing various existing studies, it was found that by implementing blockchain technology in information systems, user satisfaction may increase due to better auditability. However, careful attention is also needed to the weaknesses and challenges associated with blockchain technology, such as scalability, efficiency, and privacy. In conclusion, the use of blockchain technology in information systems can provide significant benefits in improving security. However, comprehensive measures should be taken to address issues and adapt this technology to the specific context and existing regulations.